Repeated partial melting events in the polymetamorphic Carlos Chagas batholith : implications for the tectono-metamorphic evolution of the Araçuaí orogen (southeastern Brazil) - De Melo, Marilane Gonzaga (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.